強圧延誘起ヘテロナノ組織がオーステナイト系ステンレス鋼の力学特性に与える影響に関する結晶塑性シミュレーション - 青柳, 吉輝; 戸髙, 義一; 小林, 正和; 三浦, 博己; 渡邊, 千尋 (鉄と鋼, 2019)
Severe plastic deformation has attracted interests as one of the breakthrough procedures to improve various properties of metals and alloys. Recently, it has been revealed that heavy cold rolling of some kinds of austenitic stainless steels can cause ultrafine-grained structure comparable with those achieved by severe plastic deformation. Coarse initial grains were fragmented by deformation induced microstructure to develop heterogeneous nanostructure. Tensile strength of heterogeneous-nanostructured stainless steel exceeds 2 GPa. It is considered that high strength of heterogeneous-nanostructured metals is attributed to such peculiar microstructure with dispersed “eye-shaped twin domains”. In this study, microstructural mechanisms and factors which contribute to macroscopic strength of heterogeneous-nanostructured austenitic stainless steel were evaluated on the basis of multiscale crystal plasticity simulation. Microstructure of heavily cold-rolled SUS316LN austenitic stainless steel was investigated by transmission electron microscopy, and stress-strain curves were attained by tensile tests. It was observed that microstructure of SUS316LN manufactured by 92% cold rolling was composed of deformation nano-twins, shear bands, and lamella structure. Evaluation of mechanical properties of heterogeneous-nanostructured SUS316LN was conducted using crystal plasticity finite element simulation considering microstructural information, such as dislocation density, crystal orientation, shape of grains, and dislocation sources. Information of microstructure obtained by electron backscatter diffraction, e.g. geometry of heterogeneous nanostructures and crystal orientation, were introduced to computational models for multiscale crystal plasticity simulation. It was revealed that deformation behavior depends on the tensile direction and the strength increases with the increase of volume fraction of twin domains as well as nano-twin and lamellar inter-spacings.